Ensuring Legal Certainty of Copyright for AI-Generated Works in Indonesia - Sri Rokmahwati; Amiludin Amiludin (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2025)
The rapid advancement of Artificial Intelligence (AI) technology has significantly transformed the creative industry, enabling machines to autonomously generate original works such as music, text, and visual art. This phenomenon has posed fundamental challenges to the copyright legal framework in Indonesia, particularly concerning authorship, ownership, and the protection of AI-generated works. This study aims to examine the extent to which Indonesia’s copyright law provides legal certainty for works generated by AI, while identifying gaps and potential reforms needed to address emerging issues in the digital era. The research employs a normative legal approach through library research, analyzing relevant statutory regulations, including Law No. 28 of 2014 on Copyright, doctrinal interpretations, and comparative literature on AI and copyright. The analysis focuses on the definition of authorship, the scope of protection, and the implications of legal uncertainty regarding AI-generated works. The results reveal that Indonesia’s copyright law remains anthropocentric, as it recognizes only natural persons or legal entities as authors. Consequently, the current legal framework does not explicitly accommodate the status of AI-generated works, leading to a legal vacuum and uncertainty over copyright ownership and protection. This gap may hinder innovation, reduce legal clarity for creators, developers, and users, and create potential conflicts in the creative economy. The study concludes that Indonesia’s legal system is not yet prepared to address the challenges posed by AI-generated works. Regulatory reform is necessary to provide legal certainty, balance the interests of stakeholders, and align Indonesia’s copyright law with global developments in digital regulation.